2018
DOI: 10.1186/s12902-018-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of retinol binding protein 4 and transthyretin with triglyceride levels and insulin resistance in rural thais with high type 2 diabetes risk

Abstract: BackgroundRetinol binding protein 4 (RBP4), a protein secreted by adipocytes and bound in plasma to transthyretin (TTR), has been associated with obesity, the early phase of insulin resistance, metabolic syndrome, and type 2 diabetes mellitus. The objective of this study was to elucidate the relationship between RBP4, TTR, triglyceride (TG) and type 2 diabetes risk in rural Thailand.MethodsWe measured the serum RBP4, TTR, glucose, triglyceride and insulin levels, and glucose tolerance of 167 volunteers from Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The elevated plasma RBP4 levels were positively associated with insulin resistance; it can also cause type 2 diabetes (Kwanbunjan et al 2018). These results correspond with those of Mody and Mcilroy (2014) who reported that fenretinide reduces the serum retinol-binding protein found in the bodies of humans and rodents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The elevated plasma RBP4 levels were positively associated with insulin resistance; it can also cause type 2 diabetes (Kwanbunjan et al 2018). These results correspond with those of Mody and Mcilroy (2014) who reported that fenretinide reduces the serum retinol-binding protein found in the bodies of humans and rodents.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, studies have demonstrated that RBP expression in adipose tissue and its corresponding serum protein level are considerably increased in obese mice and humans. Additionally, the elevation in serum RBP levels was demonstrated to be a precursor of insulin resistance (Kwanbunjan et al 2018). The main capacity of RBP is thought to permit the flow of the hydrophobic nutrient, vitamin A, in blood.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the level of circulating RBP4 is often elevated in obese mice and humans and that, under these circumstances, the protein induces insulin resistance [ 7 ]. Previous studies had suggested that circulating RBP4 levels were associated with insulin resistance [ 8 ], metabolic syndrome [ 9 ], impaired glucose tolerance [ 10 ], and type 2 diabetes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the research studies have demonstrated, RBP4 is associated with insulin resistance (IR), which is further associated with chronic subclinical inflammation and can promote vascular inflammation [36,[84][85][86][87]. Moreover, RBP4 can induce IR by developing the inflammatory state in the adipose tissue due to the activation of pro-inflammatory cytokines in macrophages.…”
Section: Rbp4 and The Endotheliummentioning
confidence: 99%